Rainfall duration effect on slope stability of unsaturated silty sand soil - Prabowo, Bramantyo Eko; Rachmayani, Fitri; Adiguna, Glenn Adriel; Hamdany, Abdul Halim; Bahsan, Erly; Wijaya, Martin; Prakoso, Widjojo Adi; Rahayu, Wiwik; Gofar, Nurly; Dewangga, Eriko; Satyanaga, Alfrendo (Frontiers in Built Environment, 2026)
Landslides and slope instability events in Indonesia frequently occur during the rainy season. The relationship between rainfall and landslide activity is closely linked to the ability of rainwater to infiltrate the soil, which in turn affects slope stability. The objective of this study is to assess the duration of water infiltration in unsaturated soil conditions. Soil samples were taken from the western region of Indonesia and classified as silty sand (SM). Advanced laboratory testing was conducted to obtain the unsaturated soil properties, including soil water characteristic curve (SWCC), shrinkage curve, unsaturated permeability, and unsaturated shear strength. Few studies have examined the influence of different rainfall durations on seepage and slope stability. In this study, numerical simulations include rainfall application on the ground surface for three different durations over 1 day, that is, 6-h, 12-h, and 24-h simulations. A groundwater table was located at a depth of 5 m from the surface. The simulation results reveal increases in the groundwater level and in pore-water pressure during infiltration. This event reduces the suction force in unsaturated silty sand soil, thereby decreasing the factor of safety (FoS) in slope stability. The most significant decrease in FoS occurs in the 6-h simulation, while the effect on the safety factor in the 24-h simulation is not significant. This occurs due to the high intensity of rain during the shorter rainy period. After the rainy conditions, the factor of safety gradually rises and stabilizes on the sixth day, reaching an FoS of 1.86. This work identifies areas where silt–sand lithology predominates, along with high rainfall intensity and landslide susceptibility, providing important information to guide mitigation measures.